Implementasi Sistem Manajemen Anti Penyuapan Berbasis ISO 37001: 2016 Pada Program Magang Mahasiswa Bersertifikat di PTPN XI - Nurleila Jum'ati; Siti Wulandari; Rezki Binuntsa Mutmaina; Yani Susanti; Surya Ani Devita (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Corruption in Indonesia is very high and widespread in both state-owned and private companies. The government has made various efforts to prevent acts of corruption that can hinder the growth and continuity of national development. One of the efforts made is through the implementation of an anti-bribery management system based on ISO 37001:2016. The purpose of the internship is to find out the implementation of the anti-bribery management system at the PTPN XI head office. This study uses a qualitative approach, data collection techniques through observation, FGD, and documentation using interactive data analysis techniques (data reduction, data presentation, and concluding). SMAP's external audit results show that there are 3 minor findings related to the scope of application of the anti-bribery management system which is currently limited to the head office, while for existing business units that have not implemented an anti-bribery management system based on ISO 37001:2016, the decree is not implemented. the Whistle Blowing System (WBS) management team where the complaint center is only managed by one person which will allow for manipulation of complaint data and the bribery risk identification process and not all subsections are identified for bribery risk, risk assessment is only carried out based on the business process of the work unit in general and less specific PTPN XI has implemented an anti-bribery management system in the head office environment as evidenced by the SMAP audit process which is carried out consistently every year to realize good corporate governance.